A BIOCHEMICAL BASIS FOR THE MYELOID: LYMPHOID CELL RATIO, INCREASES IN WHICH ARE ASSOCIATED WITH POOR PROGNOSES IN NUMEROUS PATHOLOGICAL CONDITIONS. (February 2015) - Tracy, Lily; Shaw, Tim
Abstract : Background: Elevated myeloid:lymphoid cell ratios in peripheral blood, which are indicative of inflammation, have been associated with poor prognoses in a wide variety of disease states. The biochemical and physiological basis of this phenomenon has not previously been investigated. Hypothesis: Proliferation of lymphocytes is absolutely dependent on an adequate supply of pyrimidine nucleotides. Increases in the activities of thymidine phosphorylase (TP) and cytidine deaminase (CDA), two key enzymes of pyrimidine metabolism that are found in myeloid cells, are frequently associated with inflammation. Neutrophils and platelets do not proliferate but have high rates of metabolism as well as the capacity to control nucleotide supply by catabolizing essential precursors including pyrimidine nucleosides and glutamine, which is required for de novo nucleotide synthesis. Aim: To investigate the relationship between CDA and TP activities and myeloid:lymphoid cell ratios in peripheral blood. Methods: Activities of CDA and TP in whole blood samples were simultaneously quantified using a simple HPLC-based assay. Metabolic activity was assessed by resazurin reduction. Results and conclusion: Elevated neutrophil:lymphocyte ratios correlated closely with increased CDA and TP activities and increased metabolic flux, supporting the hypothesis that competition for pyrimidine nucleotide precursors is an important influence on the peripheral blood myeloid:lymphoid cell ratio.